2021
DOI: 10.3389/fpubh.2021.654362
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for a Contributory Social Health Insurance Scheme: A Survey of Rural Residents in Akwa Ibom State, Nigeria

Abstract: Background: Health insurance is seen as a pathway to achieving Universal health coverage in low- and middle-income countries. The Nigeria Government has mandated states to set up social health insurance as a mechanism to offer financial protection to her citizens. However, the design of these schemes has been left to individual states. In preparation for the set-up of a contributory social health insurance scheme in Akwa Ibom State, Nigeria. This study assesses the willingness-to-pay for a social health insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…This result was discovered to be higher than that of studies conducted in Arba Minch, Southern Ethiopia (5.9%) ( 31 ) and at St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia (17%) ( 32 ), but significantly lower than the findings of many other studies in Jimma, Southwest Ethiopia (90%) ( 13 ), Wolaita Sodo, South Ethiopia (74.4%) ( 15 ), Gondar, Northwest Ethiopia (62.0%) ( 11 ), Mekelle, Northern Ethiopia (85.3%) ( 23 ), Mujja, Ethiopia (37.6%) ( 33 ), Bahir Dar, Northwest Ethiopia (66.6%) ( 20 ), Mekelle, Northern Ethiopia (74.9%) ( 18 ), and public hospitals of Tigrai, Northern Ethiopia (35.5%) ( 34 ). When compared to other findings outside Ethiopia, such as in Akwa Ibom State, Nigeria (82%) ( 35 ), Sarawak, Malaysia (46.7%) ( 16 ), Bangladesh (67.5%) ( 36 ), Juba City, South Sudan (68%) ( 37 ), Public University in Malaysia (72.5%) ( 38 ), Pokhara Lekhnath, Nepal (51%) ( 39 ), Kampala, Uganda (91%) ( 40 ), and central Vietnam (71.6%) ( 41 ), the WTP for SHI in this study was very low. It was, however, much greater than a research conducted in Indonesia's Yogyakarta Province (1.67%) ( 42 ).…”
Section: Discussionmentioning
confidence: 64%
“…This result was discovered to be higher than that of studies conducted in Arba Minch, Southern Ethiopia (5.9%) ( 31 ) and at St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia (17%) ( 32 ), but significantly lower than the findings of many other studies in Jimma, Southwest Ethiopia (90%) ( 13 ), Wolaita Sodo, South Ethiopia (74.4%) ( 15 ), Gondar, Northwest Ethiopia (62.0%) ( 11 ), Mekelle, Northern Ethiopia (85.3%) ( 23 ), Mujja, Ethiopia (37.6%) ( 33 ), Bahir Dar, Northwest Ethiopia (66.6%) ( 20 ), Mekelle, Northern Ethiopia (74.9%) ( 18 ), and public hospitals of Tigrai, Northern Ethiopia (35.5%) ( 34 ). When compared to other findings outside Ethiopia, such as in Akwa Ibom State, Nigeria (82%) ( 35 ), Sarawak, Malaysia (46.7%) ( 16 ), Bangladesh (67.5%) ( 36 ), Juba City, South Sudan (68%) ( 37 ), Public University in Malaysia (72.5%) ( 38 ), Pokhara Lekhnath, Nepal (51%) ( 39 ), Kampala, Uganda (91%) ( 40 ), and central Vietnam (71.6%) ( 41 ), the WTP for SHI in this study was very low. It was, however, much greater than a research conducted in Indonesia's Yogyakarta Province (1.67%) ( 42 ).…”
Section: Discussionmentioning
confidence: 64%
“…In a more localized Nigerian study in the rural state of Akwa Ibom, a similar positive support of 82% were willing to pay, but only 30.1% were initially aware of SHI. Again, the support will depend strongly on the income level and family size ( 32 ). Meanwhile, the performance of the SHI scheme in Mongolia was disappointing, and only 40% were satisfied.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, teachers who were aware of the insurance had a 2.5-fold greater tendency to pay more than those who were not, according to a study conducted in Ethiopia. [32][33][34][35][36][37] The type of health insurance could explain these distinctions.…”
Section: Discussionmentioning
confidence: 99%
“…(2021), Setegn et al. (2021), and Batbold and Pu (2021) 27‐47 . However, the literature review revealed no study that examines the WTP for CHI in Iran.…”
Section: Introductionmentioning
confidence: 99%